Chronic Intermittent Ethanol Exposure Alters Stress Effects on (3α,5α)-3-hydroxy-pregnan-20-one (3α,5α-THP) Immunolabeling of Amygdala Neurons in C57BL/6J Mice - Maldonado-Devincci, Antoniette M.; Kampov-Polevoi, Alexander; McKinley, Raechel E.; Morrow, Danielle H.; O’Buckley, Todd K.; Morrow, A. Leslie (Frontiers in Cellular Neuroscience, 2016)
The GABAergic neuroactive steroid (3α,5α)-3-hydroxy-pregnan-20-one (3α,5α-THP, allopregnanolone) is decreased in various brain regions of C57BL/6J mice following exposure to an acute stressor or chronic intermittent ethanol (CIE) exposure and withdrawal. It is well established that there are complex interactions between stress and ethanol drinking, with mixed literature regarding the effects of stress on ethanol intake. However, there is little research examining how chronic ethanol exposure alters stress responses. The present work examined the impact of CIE exposure and withdrawal on changes in brain levels of 3α,5α-THP, hormonal, and behavioral responses to forced swim stress (FSS). Adult male C57BL/6J mice were exposed to four cycles of CIE to induce ethanol dependence. Following 8 or 72 hr withdrawal, mice were subjected to FSS for 10 min, and 50 min later brains were collected for immunohistochemical analysis of cellular 3α,5α-THP. Behavioral and circulating corticosterone responses to the FSS were quantified. Following 8 hr withdrawal, ethanol exposure potentiated the corticosterone response to FSS. Following 72 hr withdrawal, this difference was no longer observed. Following 8 hr withdrawal, stress-exposed mice showed no differences in immobility, swimming or struggling behavior. However, following 72 hr withdrawal, ethanol-exposed mice showed less immobility and greater swimming behavior compared to air-exposed mice. Interestingly, cellular 3α,5α-THP levels were increased in the lateral amygdala 8 hr and 72 hr post-withdrawal in stressed ethanol-exposed mice compared to ethanol-exposed/non-stressed mice. In the paraventricular nucleus of the hypothalamus, stress exposure decreased 3α,5α-THP levels compared to controls following 72 hr withdrawal, but no differences were observed 8 hr post-withdrawal. There were no differences in cellular 3α,5α-THP levels in the nucleus accumbens shell at either withdrawal time point. These data suggest that there are different mechanisms mediating hormonal, behavioral, and brain responses to stress following CIE exposure. The lateral amygdala appears to be an extremely sensitive brain region exhibiting changes in cellular 3α,5α-THP levels following CIE and exposure to swim stress. It is likely that these changes in cellular 3α,5α-THP levels in the lateral amygdala contribute to the behavioral effects observed following 72 hr withdrawal.